Využití R-materiálu v hrubozrnných asfaltových směsích - Teslík, Jozef (Vysoké učení technické v Brně. Fakulta stavební, 2024)
V diplomové práci jsou zkoumány možnosti využití R-materiálu v hrubozrnných asfaltových směsích do podkladních vrstev ACP32. Teoretická část se zabývá dostupností kameniva v České republice a také řeší problematiku výroby asfaltových směsí s vyšším obsahem R-matriálu. Rovněž se v teoretické čísti porovnává využití R-matriálů v České republice s jinými zeměmi. Praktická část se zabývá návrhem, výrobou a zkoušením vybraných směsí. Pro stanovení vlastností směsí byly vybrány zkoušky pojíždění kolem, TSRST a stanovení modulu pružnosti.

The diploma thesis examines the possibilities of using R-material in coarse-grained asphalt mixtures for ACP32 base layers. The theoretical part deals with the availability of aggregates in the Czech Republic and also solves the issue of producing asphalt mixtures with a higher content of R-material. The theoretical part also compares the use of R-materials in the Czech Republic with other countries. The practical part deals with the design, production and testing of selected mixtures. To determine the properties of the mixtures, the rolling wheel tests, TSRST and the determination of the modulus of elasticity were selected.
Use of RAP in coarse-grained asphalt mixtures
Keywords: Asfalt; asfaltová směs; asfaltový beton pro podkladní vrstvy; R-materiál; hrubozrnné kamenivo; návrh asfaltové směsi; zkouška pojíždění kolem; nízkoteplotní vlastnosti; TSRST; modul pružnosti; Bitumen; asphalt mixture; asphalt concrete for base layers; R-material; coarse aggregate; asphalt mixture design; wheel tracking; low temperature properties; TSRST; modulus of elasticity